The reluctant sheriff - Offutt, Chris, 1958- (Offutt, Chris, 1958- Mick Hardin novels, 2025)
"In this breakneck new novel in master storyteller Chris Offutt's beloved crime series, sheriff Mick Hardin navigates the treacherous terrain of a town's festering secrets and the violent forces who want to keep them hidden. Mick Hardin never wanted to be sheriff. But when his sister, Linda, is shot in the line of duty, he reluctantly steps in while she recovers. It's all business as usual, until the murder of a local bar owner draws an unlikely suspect who threatens to fan the flames of Mick's past. When two more bodies turn up, seemingly unconnected to the first, Mick is forced to reckon with the mysterious circumstances of a case not so open-and-shut as everyone believes. Meanwhile, Linda is slowly healing when a familiar business tycoon with a vested interest in her returning sooner makes it difficult for her to remain on the sidelines. The Reluctant Sheriff is a dark, bracing return to the hills of eastern Kentucky where secrets roil beneath the surface, and nothing and no one stays in the past for long"--